Value-based modeling of economic decision making in conditions of unsteady environment - Guleva, V.Yu; Kovatsev, A.N.; Surikov, A.G.; Chunaev, P.V.; Gornova, G.V. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The changing environment creates the conditions for changing people’s behavior which together can lead to crisis situations. In the case of making economic decisions, the emerging non-stationarity of the dynamics of different components of the system can represent an economic crisis. The possibility of universal human values consideration in modeling decision-making under conditions of changing environment has been studied. The internal processes of an agent prior to making a decision are reflected in the concept of Beliefs-Desires-Intentions-Actions-Reactions (BDIAR). The article reviews the regularities and existing approaches to modeling economic decisions, and proposes a new, author’s approach. The mechanisms of influence of stress on decision-making, factors of rationality limitation, and risk assessment in the context of behavioral economics are revealed. The well-known theories of the influence of values on the change in the structure of consumption in a crisis situation are considered. Ways of taking into account emotions in the architecture of the agent are shown. In the proposed model, values are considered as a social factor in decision making. Due to their subjectivity, they are presented mathematically as the basis for assessing environmental objects. The subjectivity of the objects of choice assessments is reflected in the functions of attractiveness of the objects, the functions of the agent’s state dynamics, and in the subjectivity of the decision influence on the satisfaction of the agent. A possible modification of the components of the agent model is shown, taking into account the influence of values on the dynamics of consumption. A method is proposed for taking into account values in the BDIAR architecture when modeling an agent’s decision-making where the levels of the architecture correspond to values, preference functions, and functions of the agent’s state dynamics. The pseudonymized transactional data on debit cards of the partner bank customers were analyzed separately for 2017–2019 and 2020. The subjectivity of the environment influence in a crisis situation on the dynamics of changes in values and needs for different consumer groups is demonstrated, taking into account the clustering of their behavior types. Differences in the dynamics of values at the individual level and the level of groups are shown; an increase in the priority of survival values and a different rate of return to the pre-crisis state for different behavioral groups are also shown. The results obtained are useful for developing methods for modeling economic behavior in a non-stationary external environment, in particular, in the case of crises.